Cytomegalovirus disease is associated with higher all‐cause mortality after lung transplantation despite extended antiviral prophylaxis. Issue 3 (1st March 2016) - Beam, E.; Lesnick, T.; Kremers, W.; Kennedy, C.C.; Razonable, R.R.
Abstract: Background: The duration of anticytomegalovirus (CMV) prophylaxis after lung transplantation (LT) varies among transplant centers. Methods: A retrospective review of CMV donor‐seropositive/recipient‐seronegative (D+/R−) and CMV recipient‐seropositive (R+) LT patients between January 2005 and September 2012 was performed. Starting January 2007, valganciclovir prophylaxis was given for at least 12 months (often lifelong) for CMV D+/R− and extended from three to six months for R+ LT patients. Risks of CMV infection and CMV disease, and mortality after LT, were assessed. Results: A total of 88 LT patients were studied, including 32 CMV D+/R−, and 56 R+ patients. During the follow‐up period, 11 (12.5%) patients had asymptomatic CMV infection, and nine (10.3%) developed CMV disease. CMV disease (HR, 4.189; 95% CI: 1.672–10.495; p = 0.002) and CMV infection and disease (HR, 3.775; 95% CI: 1.729–8.240; p = 0.001) were significant risk factors for mortality. Overall, no significant difference was observed in rates of CMV infection or disease among LT recipients who received shorter vs. extended CMV prophylaxis. Conclusions: Despite extended prophylaxis, LT patients remain at risk of CMV infection and disease. CMV remains associated with increased mortality after transplantation.